Commodification of Culture-Based Tourism Assets to Strengthen the Creative Economy: A Case Study in Demak Regency 2009-2021 - Arravi Rizal Firmansyah; Dewi Yuliati; Dhanang Respati Puguh (Diponegoro University, 2025)
This study examines the process of commodification of cultural-based tourism assets as a strategy to strengthen the creative economy in Demak Regency during the period 2009 to 2021. Demak Regency has a significant wealth of Islamic cultural heritage, especially the Great Mosque of Demak and the tomb of Sunan Kalijaga, but this potential has not been systematically optimized within the framework of the creative economy. The study uses historical methods, namely heuristics, criticism, interpretation and historiography using a qualitative-historical approach, namely secondary data analysis based on archival documents, libraries, regional policies, BPS data, and field studies. The main problem is the concern about the phenomenon of desacralization of commodified tourism assets. This study focuses on the commodification of religious, artistic and educational cultural tourism assets owned by Demak Regency. The results of the study indicate that the process of commodification of cultural assets in Demak Regency Demak took place in three stages. The first stage was identification and determination (2009–2013), the second stage was the development phase of cultural tourism infrastructure (2014–2018), and the third stage was the digital-based creative economy integration phase (2019–2021). This study concludes that the commodification of cultural-based tourism assets in Demak Regency has significantly contributed to increasing Regional Original Income (PAD) and strengthening the creative economy sector. However, in reality, participatory governance based on the principles of sustainable development is still needed. Sustainable tourism development must give local communities a central role in management and decision-making, which can be achieved through training and the provision of relevant job opportunities in the tourism industry. On the other hand, commodification becomes an obstacle to the tension between the authenticity of cultural values and commercial interests, which needs to be managed wisely through participatory regulations.